Pengaruh Latihan Seated Cable Row Terhadap Kekuatan Menarik Otot Lengan Dan Bahu Pada Atlet Kurash UNDIKMA Tahun 2023 - Syariofeddi, Elya Wibawa (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Arm and shoulder muscle endurance is the ability of a muscle or group of muscles to be able to contract dynamically or statically by holding a load for a relatively long time. The purpose of this study was to determine the effect of seated cable row exercises on the pulling strength of the arm and shoulder muscles in Kurash Undikma Camp athletes in 2023. This research method used an experimental method. The population in this study were all Kurash Undikma Camp athletes in 2023, totaling 11 people. Meanwhile, the sample in this study used a population study technique. The data collection techniques used in this study are the method of documentation and action tests. The data analysis used in this study was statistical analysis to obtain the arm muscle strength of the Kurash Undikma Camp athletes in 2023. The results of data analysis and the t-value test show that the t-count value is 25.68 > 2.228 so it can be interpreted that the null hypothesis (H0) is states